The Effects of Compensation, Career Development, and Transformational Leadership on Job Performance, with Job Satisfaction As An Intervening Variable, in The F&B Industry - Ruhul Atsagifah; Corry Yohana; Christian Wiradendi Wolor (Enrichment: Journal of Multidisciplinary Research and Development, 2026)
Employee job performance is a critical factor in determining organizational sustainability, particularly in the food and beverage industry, where employees face high work demands, operational pressures, and dynamic business environments. Non-operational employees play an important role in supporting organizational effectiveness through administrative management, financial control, human resource management, and operational coordination. However, PT XYZ continues to face challenges related to employee performance achievement, work productivity, target completion, and cross-functional coordination. Therefore, this study aims to examine the effects of compensation, career development, and transformational leadership on job performance, with job satisfaction as an intervening variable among non-operational employees in the food and beverage industry. This study employed a quantitative approach using a survey method. The research sample consisted of 220 non-operational employees of PT XYZ selected through proportional sampling. Data were collected using questionnaires with a five-point Likert scale and analyzed using Structural Equation Modeling (SEM) with the Partial Least Squares Structural Equation Modeling (PLS-SEM) approach. The results indicate that compensation, career development, and transformational leadership have positive and significant effects on job satisfaction and job performance. Furthermore, job satisfaction has a positive and significant effect on job performance and successfully mediates the relationships between compensation, career development, and transformational leadership and employee performance. These findings highlight that effective compensation systems, structured career development opportunities, and transformational leadership practices are essential strategies for improving employee satisfaction and performance. This research contributes to the human resource management literature by demonstrating the mediating role of job satisfaction in explaining how organizational factors enhance employee performance in the food and beverage industry.